Chemical constituents from Abies chensiensis and their antifungal activity. Issue 4 (3rd April 2023) - Wei, Wen-Jun; Gao, Kun; Si, Yan-Po; Guo, Tao
Abstract: One new (1 ) and six known cycloartane triterpenoids (2-7 ), along with seven reported abietane diterpenoids (8-14 ), were isolated from the bark of the branches of Abies chensiensis, of which compounds 2-14 were also received for the first time from the genus of Abies . Structural elucidation of all the compounds was carried out by extensive spectroscopic analyses. Additionally, the antifungal activity of isolated compounds 2 -13 was evaluated by inhibiting the growth of fungal mycelium. Among them, compounds 8 and 10 demonstrated obvious inhibitory activity against plant pathogens Fusarium avenaceum and Bipolaris sorokiniana .